Innovation in the Development of the Islamic Religious Education Curriculum in Secondary Schools - Edy, Sarwo; Sumarta, Sumarta (Research Horizon, 2024)
This research discusses innovations in the development of the Islamic Religious Education curriculum at Madrasah Aliyah Ponpes Modern Al-Mukminin, Lohbener, Indramayu. In the era of globalization and rapid technological advancement, there is an urgent need to update the curriculum to remain relevant to contemporary demands while maintaining Islamic values. This case study reveals how the integration of technology in teaching and the application of active learning methods can enhance the quality of Islamic education. The study's results indicate that these innovative approaches not only enrich students' learning experiences but also prepare them to face social and technological challenges in the future. However, the implementation of these innovations also faces challenges such as resistance from the local community and the need for teacher training. Recommendations for further research include exploring the impact of curriculum innovations in various madrasah contexts and an in-depth analysis of student learning outcomes.